Alain Badiou e il linguaggio della filosofia tra sofistica e antifilosofia - D’Aurizio, Claudio (Mechane, 2024)
In Alain Badiou’s thought, the problem of defining philosophy and the question of its position in the field of practices and knowledge is often addressed through a confrontation and a struggle with some forms of thought that entertain a close relationship with it. Since the late 1980s, following the publication of his masterpiece, Being and Event (1988), Badiou started to measure philosophy against what he calls ‘Sophistry’ and ‘Antiphilosophy’ to deeply clarify and specify his idea of what philosophy is and does. The first term, sophistry, indicates for Badiou the major adversary of philosophical thought. The paper dwells on certain aspects of the relationship that philosophical practice entertains with these two categories starting from the question of language. This allows to set up some conceptual problems and clarify the theoretical stakes that they contain. Some of the questions that this attempt would like to address are the following: is there a specific language of philosophy? And what are its specific elements? What relations exist between the language of philosophy and the languages of poetry and mathematics (which for Badiou play a crucial role in the emergence of philosophy itself)?